2007
DOI: 10.1108/01437720710778402
|View full text |Cite
|
Sign up to set email alerts
|

e‐HRM in Mexico: adapting innovations for global competitiveness

Abstract: Purpose -Using information and communication technologies to deliver human resource services (also known as e-HRM) has become an important strategy for firms seeking to achieve a competitive advantage. A case-based study was carried out with the purpose of investigating how four of the most competitive Mexican firms are implementing their e-HRM strategy. Design/methodology/approach -Literature from e-HRM and human resource management in Latin America is reviewed and integrated. Four case studies developed in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 12 publications
2
61
0
4
Order By: Relevance
“…using a 2 × 2 experimental design the researchers examined the effects of (a) ability to choose the type of hrm system to which data would be disclosed (choice vs. no choice), and (b) type of information disclosed (medical vs. non-medical) on invasiveness and service satisfaction. study 1 used 71 and study 2 used 68 employed participants 2009 Beulen, e. organizational size (Ball, 2001;chapman & Webster, 2003;ngai & Wat, 2006;strohmeier & Kabst, 2009;Teo et al, 2007) sector (Tomeski & lazarus,1974) Departmental size of hr, Is, hrIs (haines & Petit, 1997) sector (olivas-lujan et al, 2007;Panayotopoulou et al, 2007;strohmeier & Kabst, 2009) sector (martinsons, 1994) sector characteristics and culture (Panayotopoulou et al, 2007) age of hrIs department (haines & Petit, 1997) organizational subsidy/branch (Voermans & van Veldhoven, 2007) Planning and project management traditions Integration of hr plan with corporate plan cooperation among departments (Broderick & Boudreau, 1992;Kossek et al, 1994) cooperation among departments, especially hr and IT (Panayotopoulou et al, 2007) mapping hr processes (Tansley & Watson, 2000) cross-functional project team …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…using a 2 × 2 experimental design the researchers examined the effects of (a) ability to choose the type of hrm system to which data would be disclosed (choice vs. no choice), and (b) type of information disclosed (medical vs. non-medical) on invasiveness and service satisfaction. study 1 used 71 and study 2 used 68 employed participants 2009 Beulen, e. organizational size (Ball, 2001;chapman & Webster, 2003;ngai & Wat, 2006;strohmeier & Kabst, 2009;Teo et al, 2007) sector (Tomeski & lazarus,1974) Departmental size of hr, Is, hrIs (haines & Petit, 1997) sector (olivas-lujan et al, 2007;Panayotopoulou et al, 2007;strohmeier & Kabst, 2009) sector (martinsons, 1994) sector characteristics and culture (Panayotopoulou et al, 2007) age of hrIs department (haines & Petit, 1997) organizational subsidy/branch (Voermans & van Veldhoven, 2007) Planning and project management traditions Integration of hr plan with corporate plan cooperation among departments (Broderick & Boudreau, 1992;Kossek et al, 1994) cooperation among departments, especially hr and IT (Panayotopoulou et al, 2007) mapping hr processes (Tansley & Watson, 2000) cross-functional project team …”
Section: Resultsmentioning
confidence: 99%
“…Stakeholder commitment to organizations' long-term goals supported by e-HRM strategizing has become progressively relevant (Olivas-Lujan et al, 2007). Thus communication about intended e-HRM use is important (Beulen, 2009); organizations should actively collect feedback from users who are impacted in their jobs by new technology before, during and after adoption (Alleyne et al, 2007).…”
Section: People Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to factors that might affect e-HRM acceptance, several studies identified contexts or resources important for e-HRM to be associated with strategic outcomes. These contextual factors included organizational size [16,41] union presence [13]; environmental infrastructure [27] and national culture [27].…”
Section: E-hrm and Strategic Hrm : Contextual Factorsmentioning
confidence: 99%
“…As a result, it is very important to apply the use of electronic technologies in the business aiming to greatly develop the skills and abilities of the employees while facilitating complicated work processes [35], [36]. Above all, today"s common human resources management has been expected to be developed to the complete e-HRM with faster and better business efficiency.…”
Section: Recommendationmentioning
confidence: 99%